2015
DOI: 10.1111/ced.12605
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of nitric oxide in serotonin-induced scratching in mice

Abstract: We show for the first time that the scratching induced by intradermal serotonin is mediated by NOS, especially iNOS, activation. We conclude that NO may play a role in mediating itch responses. NO and NOS could be new targets for antipruritic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Our studies in BMDMs and BMMCs confirm that overexpression of GCH1 enhances BH4, NO and H 2 O 2 release and mast cell degranulation, but the downstream path from BH4 to degranulation is still unknown. It has been shown that balances of NO/H 2 O 2 impact on the release of biogenic amines from mast cells in itching models suggesting a redox dependent mechanism. It is noteworthy that protein kinase C dependent degranulation involves phosphorylation, hence activation of GCH1 suggesting that BH4 is produced on PKC activation to replenish the mediator content of secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies in BMDMs and BMMCs confirm that overexpression of GCH1 enhances BH4, NO and H 2 O 2 release and mast cell degranulation, but the downstream path from BH4 to degranulation is still unknown. It has been shown that balances of NO/H 2 O 2 impact on the release of biogenic amines from mast cells in itching models suggesting a redox dependent mechanism. It is noteworthy that protein kinase C dependent degranulation involves phosphorylation, hence activation of GCH1 suggesting that BH4 is produced on PKC activation to replenish the mediator content of secretory vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of this pathway is also associated with increased production of NO (28). NO is associated with itch while inhibition of NOS suppresses itch (25, 26, 30). We reported recently that the NO/cGMP pathway participates in CQ-induced itch (30).…”
Section: Discussionmentioning
confidence: 99%
“…NO functions as a neurotransmitter in itch (25, 26, 38, 51). Similar to our findings with CQ, previous studies have shown that NO enhances substance P-induced itch in mice (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantageous property of PPAR-γ agonists on itching in various dermatological disorders has been reported by many clinical studies (Ellis et al, 2000;Pershadsingh et al, 1998;Sepmeyer et al, 2007). Our previous experimental study demonstrated that chliorquine (Foroutan et al,6 2015) serotonin can induce scratching in mice (Ostadhadi et al, 2015a;Ostadhadi et al, 2015b;Rajaba et al, 2014) and the protective anti-scratching effect of pioglitazone in serotonin-induced scratching is mediated through PPAR-γ receptor and is possibly nitric oxide dependent (Rajaba et al, 2014). However future studies are required in order to elaborate the possible peripheral and/or central anti-pruritic mechanisms of PPAR-γ (Fig.…”
Section: Ppar-γ and Pruritusmentioning
confidence: 87%